2011
DOI: 10.1380/ejssnt.2011.15
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution and AFM Observation of Photosynthetic Membrane Protein Assembly in Planar Lipid Bilayers

Abstract: In purple photosynthetic bacteria, light-harvesting complex 2 (LH2) and the light harvesting-reaction center complex (LH1-RC) play the key roles of capturing and transferring light energy and subsequent charge separation. These photosynthetic apparatuses form a molecular assembly; however, how the assembly influences the efficiency of energy conversion is not yet clear. To address this issue, direct observation of the assembly at the molecular level is necessary to analyze its function. In this study, we recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…We found that the number of H-subunits decreased after several imaging scans, indicating that the H-subunits are pulled out by the AFM tip, as previously described. , Considering this loss of H-subunits, LH1-RC complexes in the reconstituted membrane are predominantly oriented toward the H-subunit side (cytoplasmic side), as depicted in Figure B. This is consistent with our previous reports that showed a uniform orientation of LH1-RC complexes in a lipid membrane. , Figure C shows an AFM image of reconstituted LH1-RC under ambient air conditions (similar to that of C-AFM measurement). Patches of the LH1-RC-reconstituted membrane with a thickness of ∼7 nm were observed (height profile (ii)).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…We found that the number of H-subunits decreased after several imaging scans, indicating that the H-subunits are pulled out by the AFM tip, as previously described. , Considering this loss of H-subunits, LH1-RC complexes in the reconstituted membrane are predominantly oriented toward the H-subunit side (cytoplasmic side), as depicted in Figure B. This is consistent with our previous reports that showed a uniform orientation of LH1-RC complexes in a lipid membrane. , Figure C shows an AFM image of reconstituted LH1-RC under ambient air conditions (similar to that of C-AFM measurement). Patches of the LH1-RC-reconstituted membrane with a thickness of ∼7 nm were observed (height profile (ii)).…”
supporting
confidence: 90%
“…AFM Observation of LH1-RC in Reconstituted Membranes . LH1-RC reconstituted in the lipid bilayer was observed by AFM (Picoplus5500  Molecular Imaging) using AAC mode at ambient temperature. The reconstituted membrane solution was placed on a freshly cleaved mica surface, followed by the addition of an MgCl 2 solution; the membranes (either lipid/the LH1-RC core complex = 35 or 50) were absorbed onto mica surface via Mg 2+ . After ∼1 h of incubation, the solution was gently replaced with Milli-Q water, followed by water removal under a gentle stream of air to yield planar membranes.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Liposome Extension on the Mica Surface and AFM Observation . Flat lipid bilayers on a mica surface were prepared using the vesicle fusion method. The proteoliposomal suspension was placed on a mica substrate with a MgCl 2 solution. After ∼15 min of incubation, the solution was gently replaced with buffer at a pH of 4.0 (10 mM succinic acid pH 4.0, 300 mM KCl) or pH 7.5 (10 mM HEPES pH 7.5, 300 mM KCl).…”
Section: Methodsmentioning
confidence: 99%
“…Flat lipid bilayers on a mica surface were prepered with vesicle fusion method3940. The proteoliposomal suspension was put onto a mica substrate after the addition of MgCl 2 solution.…”
Section: Methodsmentioning
confidence: 99%